THE GRAMMAR OF DISNEY LONG ANIMATIONS: A STRUCTURALIST READING - Santosa, Vyrna (k@ta: A Biannual Publication on the Study of Language and Literature, 2005)
Treating several animated films as texts, the analysis of this particular genre of entertainment is using structuralist narratology, which is applied to establish a general grammar of Disney long animations by revealing the underlying rules governing the tilm narratives. Discussing the typical characters and actions, the construction of "function", and the significant actions which shape the story, this study reveals the six actant/roles based on the prescribed characterization, three basic patterns of how each actant is related to one another, and the twelve sets of basic arrangement of functions as the single basic structure of all Disney long animations. This study proves how loyal and consistent the creators of Disney long animations are toward the underlying basic structure of the story.